1998
DOI: 10.1016/s0954-6111(98)90424-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COPD patients performing nocturnal non-invasive mechanical ventilation

Abstract: The role of non-invasive nocturnal domiciliary ventilation (NNV) in chronic obstructive pulmonary disease (COPD) patients with chronic hypercapnia is still discussed. The aims of this study were to evaluate the long-term survival, the clinical effectiveness and side-effects of NNV in these patients. Forty-nine stable hypercapnic COPD patients on long-term oxygen therapy (LTOT) were assigned to two groups: in Group 1, 28 patients performed NNV by pressure support modality in addition to LTOT; in Group 2, 21 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
3
40
0
1
Order By: Relevance
“…An Italian 2-yr multicentric trial showed that NPPV plus LTOT improved daytime Pa,CO 2 , dyspnoea and QoL, although survival was similar to that in the control (LTOT alone) group [84]. In this and another observational controlled study [85], ICU admissions were reduced during NPPV compared with the LTOT regimen. In one randomised controlled study, home nocturnal NPPV, added to daytime exercise training, significantly increased exercise capacity and QoL compared with exercise training alone [86].…”
Section: Lung Transplantationmentioning
confidence: 57%
“…An Italian 2-yr multicentric trial showed that NPPV plus LTOT improved daytime Pa,CO 2 , dyspnoea and QoL, although survival was similar to that in the control (LTOT alone) group [84]. In this and another observational controlled study [85], ICU admissions were reduced during NPPV compared with the LTOT regimen. In one randomised controlled study, home nocturnal NPPV, added to daytime exercise training, significantly increased exercise capacity and QoL compared with exercise training alone [86].…”
Section: Lung Transplantationmentioning
confidence: 57%
“…Most studies provided no information. One RCT 92 stated that all patients had had previous exacerbations and three non-randomised controlled studies in stable populations 89,93,94 specified at least one previous admission because of severe exacerbation.…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
“…76,78,81,84,92 Only four out of nine 89,[93][94][95] non-randomised controlled studies provided clear details.…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations